Knowledge and attitudes of employees at the Faculty of Medicine Foča about the concept and ethical issues in genetics - Nikolina Elez-Burnjaković; Milena Dubravac Tanasković; Milan Kulić; Radmila Balaban Đurević; Aleksandar Tanović; Kristina Drašković Mališ; Biljana Vasiljević; Bojan Joksimović (Биомедицинска истраживања, 2023)
Introduction: The improvement of new genetic testing strategies are getting to be progressively integrated into different parts of medicine. Progress has not been accompanied by the satisfactory level of genetic education but it has been accompanied with many ethical issues concering testing among medical students, doctors and the common population. Subsequently, the requirements for an adequate education in genetics for each group are expanding. The main goal of this paper is to examine attitudes regarding different aspects of genetic testing, and to determine differences in attitudes with respect to socio-demographic characteristics among the employees at the Faculty of Medicine in Foča, University of East Sarajevo. Methods: Sixty-one employees of four study programs of the Faculty of Medicine in Foča participated in the research. An anonymous survey was conducted based on the voluntary consent of the respondents. It included two parts. The first part of the survey included socio-demographic questions (age, gender, educational level). The second part consisted of eight questions about genetic testing, which were related to the ethical justification of genetic testing. Results: Out of the total number of respondents, 90.2% of respondents would undergo genetic testing for health reasons. A significantly higher number of respondents who had a master’s degree (96.2%) would undergo genetic testing, compared to (88.9%) respondents who had an undergraduate degree (p=0.001). A significantly larger number of older respondents (29.6% over the age of 36) considered abortion justified in case of prenatal diagnosis of cancer at a later age, compared to 8.8% of the respondents belonging to the younger age group (from 26 to 35) (p=0.036). Conclusion: We have shown that there is a different understanding among the population of different educational status and different age. Further on in the near future, it is our opinion that seminars should be organized regarding this science, in order to promote its importance.
Keywords: genetic testing; ethics; abortion